Self-Efficacy, Mathematical Reasoning, and Mathematics Anxiety among Junior High Students: A Moderated Mediation Study - Wahidah, Fatin Rohmah Nur; Zakyatunissa, Zahra; Wijaya, Tommy Tanu (AlphaMath : Journal of Mathematics Education, 2026)
Mathematics anxiety is a persistent psychological barrier that negatively affects students’ learning processes and academic performance in mathematics. While previous studies have examined psychological and cognitive predictors of mathematics anxiety, limited research has explored their interaction using an integrative moderated mediation framework. Using a cross-sectional design, data were collected from 145 Grade VIII students at an Indonesian public junior high school. The relationships among variables were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that self-efficacy significantly reduces mathematics anxiety and positively predicts mathematical reasoning. Mathematical reasoning also negatively predicts mathematics anxiety and partially mediates the relationship between self-efficacy and anxiety. In addition, self-efficacy moderates the relationship between reasoning and anxiety (β = 0.149), indicating that reasoning skills are more effective at reducing anxiety when students have greater confidence in their mathematical abilities. Mediation analysis further reveals that mathematical reasoning partially mediates the relationship between self-efficacy and mathematics anxiety. These findings highlight the critical interplay between psychological and cognitive factors in mitigating mathematics anxiety, suggesting that reducing anxiety requires a dual-track approach that strengthens students’ mathematical reasoning while simultaneously fostering self-efficacy through confidence-supportive instructional practices such as problem-based and case-based learning.